اتباع الهوى في الإسلام: بين صفاء الفطرة وانحراف النفس: Following Desires in Islam: Between Purity of Nature and Deviation of the Soul - Noor, Mamoona (Al Basirah, 2025)
This study examines the concept of Hawa (desire) and the dangers of following personal whims (ittibāʿ al-hawā) in Islamic teachings, where it is regarded as one of the most destructive spiritual afflictions leading to moral deviation, ethical corruption, and indulgence in sin. Linguistically, Hawa signifies the soul’s inclination toward what it loves, while in Islamic terminology it refers to prioritizing personal desires over the rulings of Sharīʿah and sound reason. The research addresses four key questions: (1) What are the linguistic and conceptual definitions of hawā? (2) What are the spiritual and ethical consequences of following personal desires? (3) How does this phenomenon manifest in contemporary Muslim society—especially within digital platforms such as TikTok, Instagram, Facebook, Reels, and Shorts? (4) What preventive and corrective measures are proposed by Islamic scholarship? Methodologically, the study adopts a descriptive–analytical approach, drawing upon classical and modern Islamic sources, linguistic references, and contemporary research on digital behavior. The findings indicate that unrestrained desires weaken spiritual awareness, distort ethical judgment, and contribute to moral decline, particularly under the influence of social media’s culture of fame, imitation, and self-exhibition. The research further reveals that the Qur’an and Sunnah strongly condemn the pursuit of unchecked desires, emphasizing that a sound fiṭrah inclines toward truth whereas indulgence in passions blinds insight and leads to misguidance. The study recommends strengthening faith, cultivating self-discipline, promoting digital ethics, and aligning personal inclinations with divine guidance as essential strategies to resist the influence of hawā and achieve moral stability and spiritual success. Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified. Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies. Participant Consent: The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained. Data Fabrication/Falsification Statement: The author(s) declare that no data have been fabricated, falsified, or manipulated in this study. Copyright: Author(s) retains the Copyright of this article.